HUMAN CAPITAL INVESTMENT AND FIRM VALUE OF QUOTED MANUFACTURING COMPANIES IN NIGERIA - Doghudje, Ufuoma Sylvia; Ibanichuka, Emmanuel A. L.; Ogbonna, Gabriel N. (American Journals Publishing, 2023)
This study aim to explore the relationship between human capital investment and stock prices of manufacturing firms in Nigeria, focusing on the period from 2010 to 2019. Human capital investment was taken as a summation of the expenditures on health, training, and remuneration, while stock prices serve as the dependent variable. The study employs panel data from 30 quoted manufacturing companies and utilizes an ex-post facto research design. The study adopts a panel regression model, specifying that stock price is a function of human capital investment. The model is mathematically represented and tested using the Augmented Dickey-Fuller Unit Root Test for stationarity and hypothesis testing for significance. The study relies on a sample of 30 manufacturing companies, selected using a convenience sample size determined by data availability. The Augmented Dickey-Fuller test established that both variables were stationary, making them apt for panel regression analysis. However, the results of hypothesis testing indicated that there is no statistically significant relationship between human capital investment and stock prices for the sampled companies. The calculated t-statistic (0.1313) and p-value (0.8956) failed to meet the criteria for rejecting the null hypothesis. The findings challenge traditional accounting practices that assume a direct, positive relationship between human capital investment and stock prices. This calls for a reevaluation of how such expenditures are reported and how their return on investment is calculated. Contrary to widely held beliefs and existing literature, the study reveals that human capital investments, specifically in health, training, and remuneration, do not significantly impact the stock prices of manufacturing firms in Nigeria for the period under investigation. This insight necessitates a rethinking of the paradigms surrounding human capital investments and their influence on firm value, particularly in a developing economy like Nigeria.
Keywords: Human Capital Investment, Stock Prices, Manufacturing Firms, Panel Regression, Nigeria, Accounting Implications.